2022
DOI: 10.1186/s12964-022-00964-7
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress targeted therapy for breast cancer

Abstract: Recurrence, metastasis, and drug resistance are still big challenges in breast cancer therapy. Internal and external stresses have been proven to substantially facilitate breast cancer progression through molecular and systemic mechanisms. For example, endoplasmic reticulum stress (ERS) results in activation of the unfolded protein response (UPR), which are considered an important cellular stress response. More and more reports indicate its key role in protein homeostasis and other diverse functions involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 101 publications
0
9
0
Order By: Relevance
“…ER stress is a double-edged sword ( 17 ). On the one hand, ER stress is important for tumor microenvironmental homeostasis and tumor growth inhibition; on the other hand, sustained ER stress can initiate multiple signaling pathways to promote tumor cell death ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…ER stress is a double-edged sword ( 17 ). On the one hand, ER stress is important for tumor microenvironmental homeostasis and tumor growth inhibition; on the other hand, sustained ER stress can initiate multiple signaling pathways to promote tumor cell death ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have shown that ER stress is involved in many diseases, such as central nervous system diseases, in ammation, cancer, and so on [15]. In cancer cells, ER stress may activate autophagy, degrade misfolded proteins in cells and reuse them, which is a way to survive under stress, therefore, ER stress has become a therapeutic target for the treatment of many cancers [16,17]. Autophagy is an evolutionarily conserved membrane transport and degradation process, which operates at basal levels under normal conditions as a means of degrading cytosolic proteins and organelles.…”
Section: Discussionmentioning
confidence: 99%
“…During cellular homeostasis, this protein on ER binds to molecular chaperone Glucose‐regulated protein 78 (GRP78). However, during ER stress, GRP78 gets separated from these proteins and is actively recruited to accumulate misfolded proteins (Bae et al, 2021; Cui et al, 2022; Xu et al, 2022; Zeng et al, 2020).…”
Section: Anticancer Activity Of Curcumin Analogues Via Different Mole...mentioning
confidence: 99%